1993
DOI: 10.1007/bf00014746
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the major chlorosomal bacteriochlorophylls of the green sulfur bacteria Chlorobium vibrioforme and Chlorobium phaeovibrioides; their function in lateral energy transfer

Abstract: The chlorosomal bacteriochlorophyll (BChl) composition of the green sulfur bacteria Chlorobium vibrioforme and Chlorobium phaeovibrioides was investigated by means of normal-phase high-performance liquid chromatography. From both species a number of homologues was isolated, which were identified by absorption and (252)Cf-plasma desorption mass spectroscopy. Besides BChl d, C. vibrioforme contained a significant amount of BChl c, which may provide an explanation for the previous observation of at least two spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…These results illustrate the adaptability of the anoxygenic photosynthetic community to very low incident light levels. Although farnesol is the main alcohol esterifying the bacteriochlorophylls at position C-17, earlier studies have shown that a number of other alcohols are present in natural samples (Caple et al, 1978;Otte et al, 1993) depending on growth conditions, light intensity and stage of development of the cell (Borrego and Garcia-Gil, 1995;Airs et al, 2001b). Massé et al (2004) reported that in cultured Cb.…”
Section: Anoxygenic Photosynthesis In Tillari and Selaulim Reservoirsmentioning
confidence: 99%
“…These results illustrate the adaptability of the anoxygenic photosynthetic community to very low incident light levels. Although farnesol is the main alcohol esterifying the bacteriochlorophylls at position C-17, earlier studies have shown that a number of other alcohols are present in natural samples (Caple et al, 1978;Otte et al, 1993) depending on growth conditions, light intensity and stage of development of the cell (Borrego and Garcia-Gil, 1995;Airs et al, 2001b). Massé et al (2004) reported that in cultured Cb.…”
Section: Anoxygenic Photosynthesis In Tillari and Selaulim Reservoirsmentioning
confidence: 99%
“…Our observation is consistent with Pancost et al (2004) which reported methyl isobutyl maleimide, a degradation product of bacteriochlorophylls d and e, in OAE-2 sediments from central Italy and Tunisia. Since both bacteriochlorophylls d and e are restricted to anaerobic green sulfur bacteria (e.g., Otte et al, 1993;Glaeser et al, 2002;Nakajima et al, 2003), the presence of derivatives of these bacteriochlorophylls indicates that at least the base of photic zone was anaerobic at these sites during the OAE-2. This consideration supports previous observations of Sinninghe Damsté and Köster (1998) who reported derivatives of isorenieratene, a carotenoid pigment of green sulfur bacteria in the Bonarelli black shale.…”
Section: Geoporphyrins In Bonarelli Black Shalementioning
confidence: 99%
“…This is considered to affect altered spectral properties by modulating the in vitro aggregation properties of the chromophores. However, structural studies of the demetallated derivatives of the homologues [104] from Chlorobium vibrioforme indicate substantial alterations to the macrocycle conformation, which may contribute to the red-shift of the low-light chlorosomes, although analysis of the spectral properties of the isolated chromophores [262] did not show any systematic variation corresponding to the extent of methylation. Additionally, model compounds have indicated that the C20-methyl substituent induces local nonplanarity at this position, which may contribute to the 10 nm red shift of BChl c relative to BChl d (see Chapter 2.3) [46,96].…”
Section: Bchl Lamellar Sheetsmentioning
confidence: 94%